A Clinical Review of Return-to-Play Considerations After Anterior Shoulder Dislocation. (July 2016) - Watson, Scott; Allen, Benjamin; Grant, John A.
Context: Shoulder dislocations are common in contact sports, yet guidelines regarding the best treatment strategy and time to return to play have not been clearly defined. Evidence Acquisition: Electronic databases, including PubMed, MEDLINE, and Embase, were reviewed for the years 1980 through 2015. Study Design: Clinical review. Level of Evidence: Level 4. Results: Much has been published about return to play after anterior shoulder dislocation, but almost all is derived from expert opinion and clinical experience rather than from well-designed studies. Recommendations vary and differ depending on age, sex, type of sport, position of the athlete, time in the sport's season, and associated pathology. Despite a lack of consensus and specific recommendations, there is agreement that before being allowed to return to sport, athletes should be pain free and demonstrate symmetric shoulder and bilateral scapular strength, with functional range of motion that allows sport-specific participation. Return to play usually occurs 2 to 3 weeks from the time of injury. Athletes with in-season shoulder instability returning to sport have demonstrated recurrence rates ranging from 37% to 90%. Increased bone loss, recurrent instability, and injury occurring near the end of season are all indications that may push surgeons and athletes toward earlier surgical intervention. Conclusion: Most athletes are able to return to play within 2 to 3 weeks but there is a high risk of recurrent instability.